Role of hepatitis b and hepatits c virus coinfection in tb development - Lestari, Pudji; Rahmatullah, Ivan; Susanti, Dwi (Folia Medica Indonesiana, 2017)
Tuberculosis developed differently in each individual. The role of HIV in the disease development is widely known unlike the role of Hepatitis B and Hepatitis C infection. Therefore, this study is aimed at to describe the role of those co-infections in the TB development. The study employed observational – case control design with two groups, case and control group. Data collection include TB condition, whether latent or manifest, and history of Hepatitis B and Hepatitis C co-infection. The study successfully recruited the total of 32 respondents in each group. At the case group, the number of male and respondent is 19 and 13. Meanwhile, at the control group the number male respondent is 10 and the female respondent is 22. The study found that 20 and 12 respondents were positive Hepatitis B at the case and the control group. Chi-square test resulted significant different between two groups (P=0.0455 and a =0.05) with odd ratio p=0.479. Meanwhile, the study only tested one respondent with positive Hepatitis C at case group and one at control group. Comparison analysis found no significant different between groups (P=1 and a =0.05). This study reveals that TB patients are more likely to have history of Hepatitis B 2.7 times than those at the control group with the same infection but without TB development. Therefore, the possibility of Hepatitis B co-infection has role in the TB manifestation, but not for Hepatitis C co-infection.